Popping expansion and yield responses of popcorn cultivars under different row spacings and plant populations - Rossato Junior, José Antonio De Souza; Cazetta, Disnei Amélio [UNESP]; Barbosa, José Carlos [UNESP]; Fornasieri Filho, Domingos [UNESP] (Empresa Brasileira de Pesquisa Agropecuária (EMBRAPA), 2013)
The objective of this work was to evaluate the agronomic traits and the popping expansion index of three Brazilian popcorn cultivars under different row spacings and plant populations. The trials were performed during two crop seasons, under field conditions. The experimental design used was a randomized complete block, in a split-split plot, with 27 treatments and four replicates. Treatments were represented in a triple factorial arrangement: three row spacings (0.40, 0.60, and 0.80 m), three plant populations (40,000, 60,000, and 80,000 plants per hectare), and three popcorn cultivars (IAC-TC 01, IAC 12, and Zelia). The increase in plant population causes a reduction in the number of grains per ear, lower prolificacy, and grain weight loss. Cultivar grain yield is affected by row spacing and popcorn plant population. Cultivar IAC 12 shows highest grain yield under row spacings of 0.40 and 0.60 m and plant population between 60,000 and 80,000 plants per hectare. The popping expansion index is not affected by row spacing or plant population.

O objetivo deste trabalho foi avaliar os caracteres agronômicos e o índice de capacidade de expansão de três cultivares de milho-pipoca brasileiras sob diferentes espaçamentos entre linhas e populações de plantas. Os ensaios foram realizados durante dois anos agrícolas, em condições de campo. Utilizou-se o delineamento experimental de blocos ao acaso, com parcelas subsubdivididas, 27 tratamentos e quatro repetições. Os tratamentos foram representados em arranjo fatorial triplo: três espaçamentos entre as linhas (0,40, 0,60 e 0,80 m), três populações de plantas (40.000, 60.000 e 80.000 plantas por hectare) e três cultivares de milho-pipoca (IAC-TC 01, IAC 12 e Zelia). O aumento da população de plantas ocasiona redução no número de grãos por espiga, menor prolificidade e perda de massa de grãos. O rendimento de grãos das cultivares é afetado pelos espaçamentos entre as linhas e a população de plantas de milho-pipoca. A cultivar IAC 12 apresenta maior produtividade de grãos sob os espaçamentos de 0,40 e 0,60 m e a população de plantas entre 60.000 e 80.000 plantas por hectare. O índice de capacidade de expansão não é afetado pelo espaçamento ou pela população de plantas.
Capacidade de expansão e produtividade de cultivares de milho-pipoca sob diferentes espaçamentos entre as linhas e população de plantas
Keywords: Zea mays; Plant density; popping expansion index; spatial arrangement; Zea mays; Densidade de plantas; índice de capacidade de expansão; arranjo espacial